BENEFITS OF ORGANIC MULSE ON GROWTH CRISAN ORNAMENTAL PLANTS (Chrysanthemum sp.) - Puteri M. V. Wajong; Diana D. Pioh (Jurnal Agroekoteknologi Terapan, 2020)
The use of organic mulch to currently be one of the alternatives that is in demand by farmers. There are several reasons that support the utilization of mulch, namely : (a) protect the land from the grain rain, so that erosion can be reduced, the soil is not easy to be a solid; (b) reduce evaporation (evaporation), is very useful in the dry season due to the utilization of water (soil moisture) to be more efficient; (c) create environmental conditions (in the soil) good for the activity of soil microorganisms; (d) after the decaying mulch material will increase the content of soil organic matter; and (e) suppress the growth of weeds (Abdurachman et al., 2005).The prospect of cultivating chrysanthemum as a cut flower is very good, because it has a very potential market, because the ornamental chrysanthemum plant is one of the most important and popular cut flower plants in the world. Among these potential markets are Hong Kong, Malaysia, Japan, Singapore and so on (Sanjaya et al, 2012).Keywords: Mulch; Weeds; Chrysanthemum PlantsAbstrakPenggunaan mulsa organik hingga saat ini menjadi salah satu alternatif yang sangat diminati oleh petani. Ada beberapa alasan yang mendukung pemanfaatan mulsa yaitu : (a) melindungi tanah dari butir-butir hujan, sehingga erosi dapat dikurangi, tanah tidak mudah menjadi padat; (b) mengurangi penguapan (evaporasi), ini sangat bermanfaat pada musim kemarau karena pemanfaatan air (lengas tanah) menjadi lebih efisien; (c) menciptakan kondisi lingkungan (dalam tanah) yang baik bagi aktivitas mikroorganisme tanah; (d) setelah melapuk bahan mulsa akan meningkatkan kandungan bahan organik tanah; dan (e) menekan pertumbuhan gulma (Abdurachman et al., 2005). Prospek budidaya krisan sebagai bunga potong sangatlah bagus, karena memiliki pasar yang sangat potensial, karena tanaman hias krisan merupakan salah satu tanaman bunga potong yang penting dan digemari di dunia. Diantara pasar potensial tersebut adalah Hongkong, Malaysia, Jepang, Singapura dan sebagainya (Sanjaya et al,, 2012).Kata Kunci: Mulsa; Gulma; Tanaman Krisan